Analysis of Changes in Work Environment, Mental Health Program, and Leadership Support to Employee Loyalty in Start-Up Companies in East Java - Purnomo, Yudiyanto Joko; Darlin, Evalina; Haryanti, Titik (West Science Social and Humanities Studies, 2024)
This study examines the impact of changes in the work environment, mental health programs, and leadership support on employee loyalty in start-up companies in East Java. Employing a quantitative research design, data were collected from 68 respondents using a structured questionnaire with a Likert scale (1-5). The data were analyzed using SPSS version 25, utilizing descriptive statistics, reliability testing, and multiple linear regression. The findings reveal that all three factors significantly influence employee loyalty, with leadership support having the strongest impact. The study underscores the importance of integrating adaptable work environments, robust mental health initiatives, and transformational leadership practices to enhance loyalty in the dynamic start-up ecosystem. These insights provide practical guidance for start-up managers in fostering employee retention and organizational success.